Impacts of Modernization in Changing Life of Magar Community of Baglung - Acharya, Umesh (Research Nepal Journal of Development Studies, 2021)
The main objective of this paper, entitled “Changing Life of the Magar Community of Baglung” is to analyze the impacts of modernization on the Magar community. This study shows how modernization has affected the social and economic status of Magars of Baglung district. Besides, the paper scrutinizes the implications of modernization in their cultural and political affairs. The finding of the paper demonstrates the vulnerability of cultural identity of the community due to the huge dominance of fanciful cultures. The study has employed both primary and secondary data to justify how the Magar community is losing its traditions and is inclined to adapting the outside cultures. From the modern perspective they are believing in scientific positivists’ approaches on living and coping strategies. On the other hand, they are forgetting qualitative aspects of identity construction.